Comprehensive dynamic on-resistance assessments in GaN-on-Si MIS-HEMTs for power switching applications. (23rd April 2018) - Chou, Po-Chien; Hsieh, Ting-En; Cheng, Stone; del Alamo, Jesús A; Chang, Edward Yi
Abstract: This study comprehensively analyzed the reliability of trapping and hot-electron effects responsible for the dynamic on-resistance (Ron) of GaN-based metal–insulator–semiconductor high electron mobility transistors. Specifically, this study performed the following analyses. First, we developed the on-the-fly Ron measurement to analyze the effects of traps during stress. With this technique, the faster one (with a pulse period of 20 ms) can characterize the degradation; the transient behavior could be monitored accurately by such short measurement pulse. Then, dynamic Ron transients were investigated under different bias conditions, including combined off state stress conditions, back-gating stress conditions, and semi-on stress conditions, in separate investigations of surface- and buffer-, and hot-electron-related trapping effects. Finally, the experiments showed that the Ron increase in semi-on state is significantly correlated with the high drain voltage and relatively high current levels (compared with the off-state current), involving the injection of greater amount of hot electrons from the channel into the AlGaN/insulator interface and the GaN buffer. These findings provide a path for device engineering to clarify the possible origins for electron traps and to accelerate the development of emerging GaN technologies.